The menu [videorecording (Blu-Ray)] - Reiss, Seth; Tracy, Will, 1983-; Fiennes, Ralph; Taylor-Joy, Anya, 1996-; Hoult, Nicholas, 1989-; Chau, Hong, 1979-; McTeer, Janet; Birney, Reed, 1954-; Light, Judith, 1949-; Leguizamo, John; Adelstein, Paul; Carrero, Aimee, 1988-; et al. (Searchlight Pictures, 2023)
A young couple travels to a faraway secluded island to eat at an exclusive restaurant where the chef has prepared an extravagant menu, with some shocking surprises.